Feedback based Waveform Switching in LTE Network to Suppress Intentional Interference - Kirushnapriya D.; Shrivastava S.; Chaudhari S.Y.; Gupta R. (My University, 2025)
LTE networks are susceptible to interference due to cell reuse factor of one. LTE networks are also vulnerable to intentional interference threats. Since LTE bandwidth is large, jammers target mostly partial band, which is sufficient to impede the UE communication. This paper suggests a method to overcome the partial band intentional interference in the downlink. Paper analyses and suggests a way for UE to report interference measurements. Algorithm to overcome interference is also formulated and discussed. Paper also suggests techniques to decide upon the waveform switching by eNodeB. © 2021 IEEE.